Psychometric Properties of a Short Version of the Barratt Impulsiveness Scale-11 among a School Sample of Portuguese Adolescents - Pechorro, Pedro (2018)
The main aim of the present study was to examine the psychometric properties of a 18-items short version of the Barratt Impulsiveness Scale - 11 short among a Portuguese school sample (N =543) of male and female adolescents. The BIS-11 short version demonstrated good psychometric properties, namely in terms of its three-factor structure, internal consistency, convergent validity, and discriminant validity. In terms of criterion-related validity positive correlations were found with Conduct Disorder symptoms, alcohol use, cannabis use, and unprotected sex (i.e., sex without using condoms). The psychometric properties of the BIS-11 short version generally justify its use among Portuguese adolescents.